Refugee protection in the framework of international humanitarian law - Ward Mazen, Ahmed Mourad (Journal of Human Sciences, 2022)
The refugee problem is one of the most complex problems at the level of the international community, as the latter contributed to setting up a legal system for the protection of refugees and finding durable and appropriate solutions for them through the adoption of the Geneva Convention Relating to the Status of Refugees of 1951 and the Protocol attached thereto of 1967, also dealt with the drafters of international humanitarian law in conventions Geneva of 1949, special protection for refugees due to armed conflict or occupation by state to state, which helped the international community in facilitating the jurisdiction of both international humanitarian law and international refugee law in considering the situation of each refugee according to his whereabouts, whether across international borders or he remained in the occupied territories And subject to the rules of international humanitarian law.